Microwave Processing of Foods: Applications and Future Perspectives - Vyas Vaibhav (International Journal of Nutritions, 2024)
This paper introduces microwave-assisted processing of foods, fundamental principles and future perspectives provides a comprehensive exploration of the evolving landscape of microwave technology in the food processing. Despite widespread use in households, the industrial application of microwave processing remains relatively untapped. The narrative delves into specific applications, such as blanching, baking, pre-cooking, thawing and tempering, pasteurization, sterilization, microwave-assisted frying, rapid extraction, drying and inactivation of microorganisms, emphasizing the rapid temperature rise achievable in materials of low thermal conductivity. As the evolution of microwave technology continues, the emerging trends and future prospects, offering a forward-looking perspective on its potential contributions to sustainable and efficient food production is discussed. However, it underscores the wide scope of microwave technologies in functional and novel food processing sectors, emphasizing ongoing research opportunities for microwave energy applications and innovative approaches. This paper serves as a comprehensive guide for researchers and food industry professionals interested in harnessing the full potential of microwave processing for the advancement of culinary science and the creation of innovative, high-quality food products. Furthermore, by exploring the synergy between microwave technology and food processing, this paper illuminates avenues for enhanced nutritional retention and flavor preservation. It also highlights the importance of optimizing microwave parameters for specific food matrices to achieve desired outcomes efficiently. As the field continues to evolve, interdisciplinary collaborations and advancements in microwave engineering promise to revolutionize food production, ensuring both sustainability and consumer satisfaction. This paper thus presents a roadmap for unlocking the untapped potential of microwave-assisted food processing.
Keywords: Food processing; Microwave Processing; Non-thermal technology